Dyed in crimson : football, faith, and remaking Harvard's America - Eleff, Zev (Urbana : University of Illinois Press, 2023)
"In 1926, Harvard athletic director Bill Bingham chose former Crimson All-American Arnold Horween as coach of the university's moribund football team. The pair instilled a fresh culture, one based on merit rather than social status, and in the virtues of honor and courage over mere winning. Yet their success challenged entrenched ideas about who belonged at Harvard and, by extension, who deserved to lay claim to the American dream. Zev Eleff tells the story of two immigrants' sons shaped by a vision of an America that rewarded any person of virtue. As a player, the Chicago-born Horween had led Harvard to its 1920 Rose Bowl victory. As a coach, he faced intractable opposition from powerful East Coast alumni because of his values and midwestern, Jewish background. Eleff traces Bingham and Horween's careers as student-athletes and their campaign to wrest control of the football program from alumni. He also looks at how Horween undermined stereotypes of Jewish masculinity and dealt with the resurgent antisemitism of the 1920s"--
The (Cinder) path to a better life -- Winning isn't everything, but it is something -- Americanization, the Jewish take on success -- Winning for winning's sake -- Football, the ultimate wargame of life -- Horween versus McMahon and rise of the National Football League -- A member of the Hebrew race to become head coach of Harvard? -- An honorable failure and satisfactory game in every way -- The crusade to keep football a game -- Conclusion -- Acknowledgments.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on January 20, 2023).
eBooks on EBSCOhost
Keywords: Horween, Arnold, -- 1898-1985.; Bingham, William J. -- 1889-1971.; Harvard University -- Football -- History -- 20th century; Harvard University; Antisemitism -- United States -- History -- 20th century; Antisémitisme -- États-Unis -- Histoire -- 20e siècle.; SPORTS & RECREATION / Football; HISTORY / United States / State & Local / New England (CT, MA, ME, NH, RI, VT); SPORTS & RECREATION / General; Antisemitism; Football; United States; Sports & active outdoor recreation; Sport; 1900-1999; Electronic books; History